Vibrational Energy Distribution Analysis (VEDA): Scopes and limitations - Jamróz, Michał H. (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2013)
•PED analysis is indispensible in modern vibrational spectroscopy laboratories.•VEDA program for PED analysis of theoretical vibrational spectra is described.•VEDA generates internal coordinates based on molecular structure.•VEDA calculates PED contributions and optimizes the set of internal coordinates.•The art of PED interpretation using VEDA is outlined. The principle of operations of the VEDA program written by the author for Potential Energy Distribution (PED) analysis of theoretical vibrational spectra is described. Nowadays, the PED analysis is indispensible tool in serious analysis of the vibrational spectra. To perform the PED analysis it is necessary to define 3N-6 linearly independent local mode coordinates. Already for 20-atomic molecules it is a difficult task. The VEDA program reads the input data automatically from the Gaussian program output files. Then, VEDA automatically proposes an introductory set of local mode coordinates. Next, the more adequate coordinates are proposed by the program and optimized to obtain maximal elements of each column (internal coordinate) of the PED matrix (the EPM parameter). The possibility for an automatic optimization of PED contributions is a unique feature of the VEDA program absent in any other programs performing PED analysis.